Experimental research on masonry wall and timber elements connection - Moreira, Susana Maria Trindade (2013)
Studies developed for the past years and recent earthquakes have brought to light the importance that efficient connections between structural elements can have in the global behaviour of the structure. Although out-of-plane mechanisms of masonry walls are considered to be local, the reality is that their occurrence can lead to total collapse of the structure. The scarcity of data, both at experimental and numerical levels, introduces an urgent need to characterize the response of connections to seismic actions and understand their impact on the overall behaviour of the structure. Therefore, a total of 15 quasi-static monotonic and cyclic pull-out tests were performed on representative wall-to-floor (timber pavement beams) and wall-to-timber framed wall connections, unstrengthened and strengthened, in order to assess their performance and allow their characterization. The analysis contemplates parameters like: failure mode, hysteretic curve, strength degradation and total energy. The study of these parameters promotes better understanding of this type of connection and also the development of design recommendations for the strengthening. As further development, the experimental data will allow calibration of representative numerical models, enabling parametric studies of material properties and formulation of backbone curves.